2010
DOI: 10.1007/s11751-010-0090-z
|View full text |Cite
|
Sign up to set email alerts
|

Upper extremity resurfacing via an expanded latissimus dorsi musculocutaneus flap for large circumferential defects: the “spiral” reconstruction technique

Abstract: We present an expanded latissimus dorsi musculocutaneus (LDMC) flap to treat circumferential upper extremity defects via resurfacing and “spiral reconstruction” in 5 patients during a 17-year period. Five patients with different indications for tissue expansion from burns to congenital hairy nevi were operated. The expansion was done in a longitudinal direction, and a rectangular tissue expander (TE) was inserted under the LD muscle to expand the flap in a longitudinal direction thereby forming a “long” flap r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…After removing duplicate entries and applying our inclusion and exclusion criteria, 14 unique articles were included in the final analysis (Table 1) [678910111213141516171819]. …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After removing duplicate entries and applying our inclusion and exclusion criteria, 14 unique articles were included in the final analysis (Table 1) [678910111213141516171819]. …”
Section: Resultsmentioning
confidence: 99%
“…Because the underlying, deeper structures such as the tendons and muscles are usually spared, functional outcomes are typically “good” or “normal” although follow-up, when available, remains limited in the literature (6 to 36 months) [679]. Functional preservation becomes increasingly challenging when Tajima 3 defects result following R0 resection for neoplastic processes, but can still be sufficiently addressed [10].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…15 Serial expansions at some point may fail to progress as expected, however, and a different strategy will be required to gain an adequately wide coverage. There are previous reposts on pre-expansion of free scapular, 16 latissimus dorsi, 17 anterolateral thigh 18 and DIEP flaps. 19 Shang et al reported the use of pre-expanded DIEP flaps, albeit pedicled, for the resurfacing of 15 patients with burn scar contracture of the upper extremities.…”
Section: Discussionmentioning
confidence: 99%